(3eONd JShjbjs - (3eMeO GHQGgje(B, (3YHjOGJs; (3GMeO eMehO RGed(B, s ((3YeGf(B:s (3OGQ hGFd(B,s, 2009)
(3ebOeI aj GdJSYjQ , JCKjQ GdHjFI GdGbJUGOjI aj YedjI GdJSYjQ , GdJSYjQ MSH GdOhQI GdGbJUGOjI h OhQI MjGI GdJSYjQ , JSjQ SdY GdeSJgdc GdfgGFj h GdUfGYj h GdNOeGJ , GdJSYjQ GdOhdj , OhQ GdOQGSGJ h GdHMhK aj YedjI GdJSYjQ , GdJSYjQ Hjf Gdeaghejf GdESdGej h GdQCSeGdj , MGdGJ aj YedjI GdJSYjQ(B.s
(3eQGLY U(B.213s
Keywords: (3COGQI GdeHjYGJs; (3GdCSYGQs; (3GdJShjbs